Dynamic properties of single and multi-bolted composite joints at different bolt-loads and elevated temperature. Issue 4 (8th August 2021) - Abdus, Salam; Cheng, Xiaoquan; Cheng, Yujia; Hu, Renwei; Muhammad, Abid
ABSTRACT: Bolted composite joints are one of the most common joining methods used in aerospace industry for joining of parts and sub-assemblies, where there is a need to transfer high load with consistency and easy to assemble/ dissemble of parts for maintenance. Bolted connection undergoes different types of vibrations during their service life, that make the pre-load on bolted joints to decrease and call for increase in dynamic loading and failure. Regular checking and tightening of bolted joints become a crucial and expensive activity to maintain the structure to perform efficiently. The natural frequency is one of the most important factors of vibration of structure that depends on the geometry and material properties of the structure. In this paper, the effect of pre-load and temperature on the natural frequency of single bolted and double-bolted joints is investigated experimentally and numerically.